Effectiveness of core needle biopsy in the diagnosis of thyroid lymphoma and anaplastic thyroid carcinoma: A systematic review and meta-analysis - Vander Poorten, Vincent; Goedseels, Nathan; Triantafyllou, Asterios; Sanabria, Alvaro; Clement, Paul M.; Cohen, Oded; Golusinski, Pawel; Guntinas-Lichius, Orlando; Piazza, Cesare; Randolph, Gregory W.; Rinaldo, Alessandra; Ronen, Ohad; et al. (Frontiers in Endocrinology, 2022)
Both anaplastic thyroid carcinoma (ATC) and thyroid lymphoma (TL) clinically present as rapidly enlarging neck masses. Unfortunately, in this situation, like in any other thyroid swelling, a routine fine-needle aspiration (FNA) cytology is the first and only diagnostic test performed at the initial contact in the average thyroid practice. FNA, however, has a low sensitivity in diagnosing ATC and TL, and by the time the often “inconclusive” result is known, precious time has evolved, before going for core-needle biopsy (CNB) or incisional biopsy (IB) as the natural next diagnostic steps. The objective of this endeavour is to determine the diagnostic value of CNB in the clinical setting of a rapidly enlarging thyroid mass, via a systematic review and meta-analysis of the available data on CNB reliability in the differential diagnosis of ATC and TL. To this end, a PubMed, Embase and Web of Science database search was performed on June 23th 2021. Population of interest comprised patients who underwent CNB for clinical or ultrasonographical suspicion of ATC or TL, patients with a final diagnosis of ATC or TL after CNB, or after IB following CNB. From a total of 17 studies, 166 patients were included. One hundred and thirty-six were diagnosed as TL and 14 as ATC following CNB. CNB, with a sensitivity and positive predictive value of 94,3% and 100% for TL and 80,1% and 100% for ATC respectively, proved to be superior to FNA (reported sensitivity for TL of 48% and for ATC of 61%). Furthermore, the need for additional diagnostic surgery after CNB was only 6.2% for TL and 17.6% for ATC. We conclude that immediately performing CNB for a suspected diagnosis of ATC and TL in a rapidly enlarging thyroid mass is more appropriate and straightforward than a stepped diagnostic pathway using FNA first and awaiting the result before doing CNB.